2020
DOI: 10.1186/s13063-020-04779-0
|View full text |Cite
|
Sign up to set email alerts
|

Does a video clip enhance recruitment into a parenting trial? Learnings from a study within a trial

Abstract: Background Reaching recruitment targets in randomised controlled trials is a challenge. Media tools are increasingly used to engage participants, yet there is a paucity of research into the use of video to optimise recruitment. We therefore tested whether adding a participant information video clip to a standard participant information sheet improved recruitment into a parenting trial. Methods One hundred seven participants were randomised to receive either a participant information sheet (n = 51) or an info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 38 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…Mattock et al suggest that several shorter videos (e.g. 30 s each) addressing different topics such as assessment, consent, and randomization may be optimal [ 26 ]. This is likely of particular importance for multisite or more complex trials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mattock et al suggest that several shorter videos (e.g. 30 s each) addressing different topics such as assessment, consent, and randomization may be optimal [ 26 ]. This is likely of particular importance for multisite or more complex trials.…”
Section: Discussionmentioning
confidence: 99%
“…Using a video for recruitment seems to be beneficial in enhancing the understanding of what participation in trials means for the participant. However, it may not necessarily translate into increased recruitment [ 26 ]. Indeed, a better understanding of what participation in a trial involves concerning e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a recent meta-analysis investigating the effect of user-tested, simplified, and clarified study information sheets on recruitment rates showed no effect [14]. Monetary incentives were found to be effective in one trial [15], whereas access to video clips with study information online [16,17] was not. However, currently there are too few studies examining each strategy for conclusions to be drawn and our understanding of how to recruit effectively to trials is limited [4,18].…”
Section: Introductionmentioning
confidence: 99%